Differential Impact of Co-expressed SP-A1/SP-A2 Protein on AM miRNome; Sex Differences - Thorenoor, Nithyananda; Kawasawa, Yuka Imamura; Gandhi, Chintan K.; Zhang, Xuesheng; Floros, Joanna (Frontiers in Immunology, 2019)
ABSTRACT In humans there are two surfactant protein A (SP-A) functional genes SFTPA1 and SFTPA2 encoding innate immune molecules, SP-A1 and SP-A2, respectively, with numerous genetic variants each. SP-A interacts and regulates many of the functions of alveolar macrophages (AM). It is shown that SP-A variants differ in their ability to regulate the AM miRNome in response to oxidative stress (OxS). Because humans have both SP-A gene products, we were interested to determine the combined effect of co-expressed SP-A1/SP-A2 (co-ex) in response to ozone (O3) induced OxS on AM miRNome. Human transgenic (hTG) mice, carrying both SP-A1/SP-A2 (6A2/1A0, co-ex) and SP-A- KO were utilized. The hTG and KO mice were exposed to filtered air (FA) or O3 and miRNA levels were measured after AM isolation with or without normalization to KO. We found: (i) The AM miRNome of co-ex males and females in response to OxS to be largely downregulated after normalization to KO, but after Bonferroni multiple comparison analysis only in females the AM miRNome remained significantly different compared to control (FA); (ii) The targets of the significantly changed miRNAs were downregulated in females and upregulated in males; (iii) Several of the validated mRNA targets were involved in pro-inflammatory response, anti-apoptosis, cell cycle, cellular growth and proliferation; (iv) The AM of SP-A2 male, shown, previously to have major effect on the male AM miRNome in response to OxS, shared similarities with the co-ex, namely in pathways involved in the pro-inflammatory response and anti-apoptosis but also exhibited differences with the cell-cycle, growth, and proliferation pathway being involved in co-ex and ROS homeostasis in SP-A2 male. We speculate that the presence of both gene products versus single gene products differentially impact the AM responses in males and females in response to OxS.